TRANSCRANIAL CEREBELLAR DIRECT CURRENT STIMULATION AND GAIT TRAINING IN CHILDREN WITH DOWN SYNDROME: RANDOMIZED CONTROLLED DOUBLE-BLIND CLINICAL TRIAL (CIPEEX, 2025)
The objective of the research project is to compare the effects of ten sessions of treadmill gait training associated with the application of active and placebo cerebellar anodal transcranial direct current stimulation (tDCSa) on the domain of Activity (mobility and functional balance) and Participation of the ICF in children with Down Syndrome (DS). This is a randomized, placebo-controlled, double-blind clinical trial involving 30 children diagnosed with DS, aged between 3 and 8 years, who meet the eligibility criteria. The participants will be evaluated one week before, one week after, and one month after the intervention, using the Timed Up and Go, 10-Meter Walk Test, Pediatric Balance Scale, and Participation and Environment Measure for Children and Youth. The experimental group will perform treadmill gait training combined with the application of active cerebellar tDCS. The control group will perform treadmill gait training associated with the application of placebo tDCS. The speed of the gait training will be established according to the child's performance in each session. tDCS will be applied with the anode electrode positioned over the cerebellar region and the cathode electrode over the central supraorbital region. The intervention will involve ten intervention sessions, with a frequency of five sessions per week, carried out over two consecutive weeks and lasting 20 minutes each. Considering the potential effect of cerebellar tDCS, it is expected that the intervention will increase the effect size of gait training in children with DS.
Keywords: Down syndrome; gait; balance; child; physiotherapy; transcranial direct current stimulation